Psychological resources, their social antecedents, and association with well-being and health behaviour in early adulthood - Ek, Ellen (Helsingin yliopisto, 2010)
The success of entering work life, young people s psychological resources and self-reported well-being were studied in a longitudinal setting from a life-span developmental-contextual perspective in early adulthood. The aim was to analyse how psychosocial characteristics in early childhood and adolescence predict successful entrance into work life, how this is associated with well-being, and to assess the level of psychological resources such as dispositional optimism, personal meaning of work and coping in early adulthood. The role of these and social support, in the relationship between regional factors (such as place of residence and migration), self-reported health and life satisfaction was studied. The association between a specific coping strategy, i.e. eating and drinking in a stressful situation and eating habits, was studied to demonstrate how coping is associated with health behaviour. Multivariate methods, including binary logistic regression analyses and ANOVA, were used for statistical analyses. The subjects were members of the Northern Finland 1966 Birth Cohort, which consists of all women and men born in 1966 in the two northernmost provinces of Finland (n= 12,058). The most recent follow-up, at the age of 31 years when 11,637 subjects were alive, took place in 1997-1998. The results show, first, that social resources in the childhood family and adolescence school achievement predict entrance into the labour market. Secondly, psychosocial resources were found to mediate the relationship between migration from rural to urban areas, and subjective well-being. Thirdly, psychological resources at entrance into the labour market were found to develop from early infancy on. They are, however, influenced later by work history. Fourthly, stress-related eating and drinking, as a way of coping, was found to be directly associated with unhealthy eating habits and alcohol use. Gender differences were found in psychosocial resources predicting, and being associated with success in entering the labour market. ...